Experimental Bothrops atrox envenomation: Efficacy of antivenom therapy and the combination of Bothrops antivenom with dexamethasone. - Gabriella Neves Leal Santos Barreto; Sâmella Silva de Oliveira; Isabelle Valle Dos Anjos; Hipocrates de Menezes Chalkidis; Rosa Helena Veras Mourão; Ana Maria Moura-; Ida Sigueko Sano-Martins; Luis Roberto de Camargo Gonçalves (Public Library of Science (PLoS), 2017)
Bothrops atrox snakes are the leading cause of snake bites in Northern Brazil. The venom of this snake is not included in the antigen pool used to obtain the Bothrops antivenom. There are discrepancies in reports on the effectiveness of this antivenom to treat victims bitten by B. atrox snakes. However, these studies were performed using a pre-incubation of the venom with the antivenom and, thus, did not simulate a true case of envenomation treatment. In addition, the local lesions induced by Bothrops venoms are not well resolved by antivenom therapy. Here, we investigated the efficacy of the Bothrops antivenom in treating the signs and symptoms caused by B. atrox venom in mice and evaluated whether the combination of dexamethasone and antivenom therapy enhanced the healing of local lesions induced by this envenomation. In animals that were administered the antivenom 10 minutes after the envenomation, we observed an important reduction of edema, dermonecrosis, and myonecrosis. When the antivenom was given 45 minutes after the envenomation, the edema and myonecrosis were reduced, and the fibrinogen levels and platelet counts were restored. The groups treated with the combination of antivenom and dexamethasone had an enhanced decrease in edema and a faster recovery of the damaged skeletal muscle. Our results show that Bothrops antivenom effectively treats the envenomation caused by Bothrops atrox and that the use of dexamethasone as an adjunct to the antivenom therapy could be useful to improve the treatment of local symptoms observed in envenomation caused by Bothrops snakes.